Functional antibody immobilization on 3-dimensional polymeric surfaces generated by reactive ion etching - Rucker, Victor C (Langmuir : the ACS journal of surfaces and colloids, 2005)
Reactive ion etching (RIE) was used to pattern antibodies onto the surfaces of polymer substrates. A low pressure, inductively coupled oxygen plasma was used to anisotropically etch 25-30 mum deep features into poly(methyl methacrylate) (PMMA), Zeonex, and polycarbonate (PC). Scanning electron microscopy and contact angle measurements show that the resulting surfaces exhibit significant microroughness and enhanced hydrophilicity. Fourier transform infrared spectroscopy suggests that, in addition to enhanced surface area, chemical modifications may contribute to antibody immobilization. Polyclonal antibodies preferentially bind to the etched areas in RIE-patterned PMMA and Zeonex substrates but localize in unetched regions of RIE-patterned PC surfaces. Simple immunoassays were performed to demonstrate a potential application for RIE-modified polymer surfaces. Antibodies specific for the capture of fluorescently labeled cholera toxin, S. aureus enterotoxin B, and B. anthracis protective antigen were immobilized onto etched PMMA surfaces and shown to specifically capture their labeled antigen from solution. This work demonstrates a potentially useful fabrication methodology for constructing antibody microarrays on plastic substrates